The duplicitous effects of COVID-19 perception on behavioural tendencies towards fashion brands on Instagram in a sub-Saharan African context - Mahmoud, Ali B.; Voutsa, Maria C.; Solakis, Konstantinos; Grigoriou, Nichoals (My University, 2022)
Purpose. Recent research has either called for investigating (Mahmoud, Hack-Polay, Grigoriou et al., 2021) or examined (Mahmoud, Ball, Rubin et al., 2021; Mason, Narcum, & Mason, 2021) consumer behaviour on social media during the coronavirus pandemic time. Thus, this study responds to those scholarly calls and efforts and investigates the moderating effects of COVID-19 perception on relationships amongst consumers’ levels of enjoyment, usefulness, satisfaction, and intentions to follow and recommend fashion brands on Instagram, a steadily growing social media platform with an estimated population of 1.44 users in the year 2025 (Statista, 2022). Methods. The study occurred in a sub-Saharan African context during the COVID-19 pandemic in 2021. The data of 310 Instagram users based in Uganda and Nigeria were analysed using a variance-based structural equation modelling. Findings. Whilst our analyses demonstrated support for previously reported results in the literature, mainly by offering evidencing the full and positive mediating role of satisfaction in transmitting the effects of enjoyment and usefulness to higher levels of intentions to follow and intentions to recommend fashion brands on Instagram, COVID-19 perception was found to lower the chances of being satisfied as a result of enjoyment, albeit the total effects of COVID-19 perception on satisfaction and ultimately the behavioural intentions of following and recommend fashion brands on Instagram. Originality. This empirical investigation bridges the research gap posited in examining the moderating role of pandemic perception in the way consumers behave towards fashion brands on social media, notably in a little researched context like sub-Saharan Africa.
Keywords: COVID-19 perception; Fashion; Pandemic; Social media marketing; Africa